Intracrystalline "geothermometry" assessed on clino and orthopyroxene bearing synthetic rocks. (15th April 2018) - Murri, M.; Cámara, F.; Adam, J.; Domeneghetti, M.C.; Alvaro, M.
Abstract: Recent discussion on the application of intracrystalline "geothermometers" based on the Fe–Mg order-disorder reaction in pyroxene in natural rocks, indicates that the available calibration equations for clino and orthopyroxenes (cpx and opx), which express the equilibrium intracrystalline Fe–Mg distribution coefficient k D (Fe–Mg) as a function of temperature, require independent validation. In this paper, we tested the available experimental calibrations for clino and orthopyroxenes by determining the site occupancies of these minerals in synthetic samples grown from a hydrous nepheline basanite in a piston-cylinder apparatus at 1050 °C at 2.0 GPa to 1170 °C at 3.0 GPa, and quenched very rapidly by shutting off the power. The site occupancies were determined by single crystal X-ray diffraction (SC-XRD) and used to calculate the closure temperature, TC, of cation ordering using available calibrations of k D (Fe–Mg) vs. T . The calculated T C values of both clino and orthopyroxenes were found to be close to the temperatures at which they were quenched, in line with expected kinetic behavior, when calibrations for cpx (Murri et al., 2016) and opx (Stimpfl et al., 2005) based on SC-XRD structure refinements were used. In particular, the smallest discrepancy between calculated and actual temperature is of the order of a few degrees (12 °C for cpx and 4 °C for opx), and the largest is of the order of tens of degrees (22 °C for cpx and 55 °C for opx). On the other hand, much lower TC s were obtained when calibrations based on Mössbauer determination of site occupancies were used. These results confirm that the two methods (i.e. SC-XRD and Mössbauer) give inherently different site occupancy data and that the same methodology should thus be used for both calibration and natural samples in the determination of cooling rate of host rocks.